Assistance of BUMDes Tirta Kamulyan Kangen Water in Bangunjiwo Village, Kasihan, Bantul, Yogyakarta - Barbara Gunawan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this activity is to increase the income of BUMDes through the Tirta Kamulyan bottled water business, which is one of the BUMDes Bangunjiwo business units. Problems in the production sector, namely the absence of a filter to filter ready-to-drink water and an unhygienic pouring process; while for the marketing field is the lack of ability of managers to market products online, besides that the packaging used is not attractive. The methods used are: 1) Procurement and training on the use of bottled drinking water filters, 2) Lectures on health protocol socialization for BUMDes managers and youth organizations, 3) Training and assistance in making product packaging labels, online product marketing, and making blocks and social media for youth groups. From the service activities, activities were held in the form of: 1) Procurement of water filters and training on the use of water filters, 2) Socialization of the Covid-19 health protocol for BUMDes managers and youth organizations, installing Covid-19 protocol banners around BUMDes, providing health protocol tools, 3) Training and assistance in the manufacture of product packaging labels, 4) Training and assistance in online product marketing; and 5) Training and assistance in making blocks and social media for youth organizations. All activities were completed and were successful, after the service program, sales of Tirta Kamulyan Kangen Water products increased by 20%.